Design and development of activity attendance monitoring system based on RFID - Ray Adderley Jm Gining; S.S.M. Fauzi; I.M. Ayub; M.N.F. Jamaluddin; Ira Puspitasari; Okfalisa Okfalisa (Institute of Advanced Engineering and Science, 2020)
Attending activities organized by the university or institution is one of the important criteria that must be fulfilled by students for multiple purposes. Whether it is by attending classes, or any other activities, the main concern is focused on the process of recording students’ attendance. The use of a paper-based manual system to record students’ attendance is still being widely used due to the lack of an e-management system. These approaches have a lot of disadvantages due to the nature of the paper which is a fragile material - also an expensive cost to procure and produce. This paper, relying on Radio Frequency Identification (RFID), designed and developed an electronic system known as Activity Attendance Monitoring System (AAMS) that utilizes readily available resource – student card, as the student identification when attending an activity. Results from the validation, execution and continuous test suggest that AAMS can be effectively implemented to monitor and record student’s attendance. The main contribution of the study is the design and development model that capable of monitoring students’ activity attendance in university activities context. Developers and researcher in the area can adopt the proposed design and development model in formulating a similar system in managing activity attendance.